Downward trends in the prevalence of childhood overweight in two pilot towns taking part in the VIASANO community‐based programme in Belgium: data from a national school health monitoring system. Issue 1 (31st March 2015) - Vinck, J.; Brohet, C.; Roillet, M.; Dramaix, M.; Borys, J.‐M.; Beysens, J.; Jacobs, N.; Jebb, S.; De Laet, C.; Nève, J.
Summary: Background: Multilevel approaches involving environmental strategies are considered to be good practice to help reduce the prevalence of childhood overweight. Objectives: The objective of this study was to evaluate the effects of VIASANO, a community‐based programme using the EPODE methodology, on the prevalence of overweight in two pilot towns in Belgium. Methods: We analysed data from a national school health monitoring system to compare changes in the prevalence of overweight and obesity over a 3‐year period (2007–2010) in children aged 3–4 and 5–6 years in the pilot towns with those of children of the same ages from the whole French‐speaking community of Belgium. Heights and weights of all participants were measured by trained school nurses using a standardized method. Results: The prevalence of overweight (−2.1%) and overweight + obesity (−2.4%) decreased in the pilot towns, but remained stable in the comparison population (+0.1% and +0.2%, respectively). After adjustment for lack of homogeneity between the study populations, there was a trend towards a decrease in overweight ( P = 0.054) and overweight + obesity ( P = 0.058) in the pilot towns compared with the general population. Conclusions: These results suggest that a community‐based programme, such as VIASANO, may be a promising strategy for reducing the prevalence of childhood overweight even over a short period of time.